Предмет: Алгебра,
автор: vladamukhametzyanova
lg(x-2)+lg(x-9)= lg 10-lg5
Ответы
Автор ответа:
0
lg (x-2)(x-9) = lg 2
x²-9x-2x+18=2
x²-11x+16 = 0
D=121-64=57
x1=(11+√57)/2
x2=(11-√57)/2 - не подходит, ибо под вторым логарифмом выражение не может быть отрицательным (11-√57)/2 - 9 < 0
ответ (11+√57)/2
x²-9x-2x+18=2
x²-11x+16 = 0
D=121-64=57
x1=(11+√57)/2
x2=(11-√57)/2 - не подходит, ибо под вторым логарифмом выражение не может быть отрицательным (11-√57)/2 - 9 < 0
ответ (11+√57)/2
Похожие вопросы
Предмет: Химия,
автор: vargageri0811
Предмет: Русский язык,
автор: kolasiko083
Предмет: Литература,
автор: ellievakmurad
Предмет: Математика,
автор: ZZZZZSWISSZZZZZ